La biblioteca del colegio San Bernardo de la compañía de Jesús en Oropesa (Toledo) - Sánchez González, Ramón (Hispania sacra, 2011)
Don Francisco Álvarez de Toledo, viceroy of Peru, founded a school where Grammar– Latin Studies, Arts and Theology were taught in his hometown of Oropesa in 1578. The Society of Jesus was entrusted with the school and it endured through time until the expulsion of the Jesuits in 1767. One of the most outstanding characteristics of the educational institution was its general library which contained over 2,000 volumes. The library, contrary to the custom of the time, was inherited by the descedants of the founder, patrons in turn of the foundation. Thanks to the existence of a complete and detailed inventory, this article analyses different aspects related to cultural history as far as books are concerned.